Pembuatan Dye Sensitized Solar Cell (DSSC) menggunakansubstrat Kaca GMR danEkstrakSirih Merah (Piper Ornatum) sebagai Dye-Sensitizer - Afrimirza, Frengky (journal of residu, 2019)
Solar cells convert sunlight energy into electrical energy, one of which is Dye Sensitized Solar Cell (DSSC). DSSCs are dye-based solar cells that absorb light. GMR (Giant Magnetoresistance) material has good electrical and magnetic properties. The coating method used is sol gel, a spin coating technique with sandwich layer type. The aim of this research is to determine the effect of the concentration of the dye solution and the effect of the time of immersion on the conversion value of solar energy into electrical energy and the value of the DSSC efficiency produced. In this research, ZnO was coated on GMR glass and as an absorbent photon, anthocyanin dye from red betel leaf extract was used. Characterization of light absorption using UV-Vis is known that light absorption in red betel leaves (Piper Ornatum)dye at wavelengths of 360 nm and 670 nm. To see the functional groups found in red betel leaves (Piper Ornatum) dye, FTIR characterization was carried out. Based on research conducted DSSC managed to convert solar energy into electrical energy where the concentration variation obtained maximum efficiency of 0.0566% at the concentration of 50% dye solution and maximum efficiency produced with variations in the length of immersion time of 0.376% with the time of immersion during 5 hours.